2007
DOI: 10.1007/s00006-007-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Quaternion Fourier Transform on Quaternion Fields and Generalizations

Abstract: Abstract. We treat the quaternionic Fourier transform (QFT) applied to quaternion fields and investigate QFT properties useful for applications. Different forms of the QFT lead us to different Plancherel theorems. We relate the QFT computation for quaternion fields to the QFT of real signals. We research the general linear (GL) transformation behavior of the QFT with matrices, Clifford geometric algebra and with examples. We finally arrive at wide-ranging non-commutative multivector FT generalizations of the Q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
162
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(163 citation statements)
references
References 23 publications
0
162
0
1
Order By: Relevance
“…It is shown that many WFT properties still hold but others have to be modified. Another generalization using the kernel of the (right-sided) quaternion Fourier transform [11,12] was introduced in [13]. In the present paper, we continue this generalization to real Clifford algebra Cl 0,n .…”
Section: Introductionmentioning
confidence: 84%
“…It is shown that many WFT properties still hold but others have to be modified. Another generalization using the kernel of the (right-sided) quaternion Fourier transform [11,12] was introduced in [13]. In the present paper, we continue this generalization to real Clifford algebra Cl 0,n .…”
Section: Introductionmentioning
confidence: 84%
“…This made possible a quaternion Fourier transform of a one-dimensional signal: [24,25], Hitzer thoroughly studied the quaternion Fourier transform (QFT) applied to quaternion-valued functions in [54]. As part of this work a quaternion split 5) was devised and applied, which led to a better understanding of GL(R 2 ) transformation properties of the QFT spectrum of two-dimensional images, including colour images, and opened the way to a generalization of the QFT concept to a full spacetime Fourier transformation (SFT) for spacetime algebra C 3,1 -valued signals.…”
Section: Quaternion Fourier Transforms (Qft)mentioning
confidence: 99%
“…So the relative order of the factors in F n {f }(ω) becomes important, see [66] for a systematic investigation and comparison. In the context of generalizing quaternion Fourier transforms (QFT) via algebra isomorphisms to higher dimensional Clifford algebras, Hitzer [54] constructed a spacetime Fourier transform (SFT) in the full algebra of spacetime C 3,1 , which includes the CFT (2.1) as a partial transform of space. Implemented analogous (isomorphic) to the orthogonal 2D planes split of quaternions, the SFT permits a natural spacetime split, which algebraically splits the SFT into right-and left propagating multivector wave packets.…”
Section: How Clifford Algebra Square Roots Of −1 Lead To Clifford Foumentioning
confidence: 99%
“…It plays an important role in quaternionic signal processing. Based on the Heisenberg type uncertainty principle for the quaternion Fourier transform (QFT) [13,14], the authors in [7] proposed a component-wise uncertainty principle associated with the CQWT.…”
Section: Introductionmentioning
confidence: 99%